Irreversible Investments and Regulatory Risk - Paolo M. Panteghini; Carlo Scarpa (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper addresses the issue of how regulatory constraints affect firm's investment choices when the firm has an option to delay investment. The RPI-x rule is compared to a profit sharing rule, which increases the x factor in case profits go beyond a given level. It is shown that a pure price cap and profit sharing are identical in their impact on investment choices: the change in the option value that we have with a profit sharing regime exactly compensates the change in the direct profitability of investment. Regulatory risk - breaching of the regulatory contract - may or may not affect negatively investment decisions. Even if a distortion exists, we show that this distortion is the same, even if a pure price cap could be considered riskier than a profit sharing rule.
Keywords: 330; regulation; investment; RPI-x; profit sharing